Neurodevelopmental follow-Up in children with intrauterine and perinatal exposure to chikungunya virus - Ferreira, Fatima Cristiane Pinho de Almeida Di Maio; Nielsen-Saines, Karin; Moreira, Maria Elisabeth Lopes; Salgado, Aline Dessimoni; Costa, Roozemeria Pereira; Campos, Simone B. de; Marschik, Dajie; Huening, Britta; Einspieler, Christa; Marschik, Peter B.; Fuller, Trevon; Brasil, Patrícia (The journal of pediatrics, 2025)
Objective To investigate the effects of intrauterine and perinatal exposure to chikungunya virus (CHIKV) on neurodevelopment in infants and toddlers. Study design We conducted a cohort study comparing children with intrauterine or perinatal exposure to maternal CHIKV infection with unexposed controls in Rio de Janeiro, Brazil. Neurodevelopment was assessed with General Movement Assessments in the first 6 months of life, and the Bayley-III Scales of Infant and Toddler Development and Modified Checklist for Autism in Toddlers for older children. Developmental delay (DD) was defined as a Bayley score less than 70 and risk of DD as a score less than 85. Results Among 60 children exposed to intrauterine or perinatal CHIKV, 20 (33%) had laboratory confirmation of CHIKV infection by reverse transcription polymerase chain reaction or immunoglobulin M serology and 40 did not; 44 exposed children (15 infected and 29 uninfected) had General Movement Assessment performed, with 19% having suboptimal or abnormal results. At 11-42 months of age, 35 exposed children and 78 unexposed controls had Bayley-III assessments. Compared with controls, exposed children had higher rates of DD (7 [20%] vs 2 [3%], P = .004) driven by the language domain, and greater risk of DD driven by motor and cognitive domains scores (10 [29%] vs 10 [13%], P = .03 and 8 [23%] vs 5 [6%], P = .02, respectively). Eight of 35 (23%), CHIKV exposed children screened positive for autism spectrum disorder. CHIKV-exposed uninfected children had 2 (9.5%) cases of DD and 5 (23.8%) cases of autism spectrum disorder. Conclusions Abnormal neurodevelopmental results were seen in both infected and uninfected children with intrauterine or perinatal CHIKV exposure. Infant neurodevelopment monitoring should be considered following exposure to maternal CHIKV infection in pregnancy to facilitate early interventions and to mitigate neurodevelopmental sequelae. (J Pediatr 2025;279:114477).
Online veröffentlicht am 27. Januar 2025, Artikelversion am 13. Februar 2025
Gesehen am 23.10.2025